Horrific Pasts and Mundane Presents: Living among the Jewish Ghosts of Warsaw and Lublin - Laura Chamberland; Hernan Tesler-Mabé (Chrześcijaństwo-Świat-Polityka)
This article represents a consideration of the way in which the Jewish past in two key areas of Poland is obfuscated by the historical processes that led to the creation and re-creation of the urban space.  Focussing on the district of Muranow in Warsaw and the Majdanek site in Lublin, the authors argue that the juxtaposition of the horrific past and a more mundane present create a destabilizing disjunction – what Suzanne Knittel calls the “historical uncanny” – that unsettles and stands in the way of a Polish reconciliation with its Jewish past.